Evaluation of dietary intake of the School of Sports Championship students - Łopacińska, Olga; Stańczyk, Katarzyna; Korn, Aleksandra; Czarnecka, Karolina; Wójcik, Emilia; Korczak, Anna; Jędrzejczyk, Justyna; Szewczyk, Oliwia; Olek, Ewa; Burda, Katarzyna; et al. (Quality in Sport, 2024)
Introduction and purpose: Nutrition plays an important role in the lives of young athletes. A well-balanced diet is crucial not only for their sports performance, but also for their proper growth and optimal health. The aim of this study is to evaluate the dietary intake of the School of Sports Championship students. A brief description of the state of knowledge: When compared to the nutritional needs of regular teenagers, young athletes have higher caloric requirements. They need to follow precise meal scheduling, must maintain proper hydration, and sometimes need to use dietary supplements. Moreover, adolescent athletes, especially females, have a higher risk of athlete triad, anemia, or eating disorders. In addition, young athletes seem to be unaware of the importance of their diet and how it directly affects their overall health and athletic performance. Conclusions: The results of this study indicate that the dietary choices of young athletes significantly affect their sports performance. We found a correlations between the duration of trainings and the intake of sequentially: protein, fiber, and vitamin D. Also, we discovered that female athletes consume less vitamin D and iron compared to male athletes, which may lead to a dangerous health implications, including anemia or the female athlete triad. However, there is a need for more prospective randomized clinical trials conducted on a larger sample size to reach final conclusions.